2007
DOI: 10.1016/j.exer.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mapping age-related elasticity changes in porcine lenses using bubble-based acoustic radiation force

Abstract: Bubble-based acoustic radiation force aims to measure highly localized tissue viscoelastic properties. In the current investigation, acoustic radiation force was applied to laser-induced bubbles to measure age-related changes in the spatial distribution of elastic properties within in vitro porcine lenses. A potential in vivo technique to map lens elasticity is crucial to understanding the onset of presbyopia and develop new treatment options. Bubble-based acoustic radiation force was investigated as a techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 40 publications
5
40
2
Order By: Relevance
“…It is reported that the lens has a Young's modulus of several tens of Pa to tens of kP. 10,11,20,21,24,27 However, most of these techniques to measure lens elasticity assume direct mechanical testing and usually can be used only in vitro. Among various techniques to measure mechanical properties of tissues noninvasively, radiation force has investigated greatly during last few decades as a means of a palpation tool for imaging soft tissues where external forces cannot reach.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that the lens has a Young's modulus of several tens of Pa to tens of kP. 10,11,20,21,24,27 However, most of these techniques to measure lens elasticity assume direct mechanical testing and usually can be used only in vitro. Among various techniques to measure mechanical properties of tissues noninvasively, radiation force has investigated greatly during last few decades as a means of a palpation tool for imaging soft tissues where external forces cannot reach.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 While laser-tissue ablation and associated formation of microbubbles play an increasingly important role in laserbased microsurgery, microbubbles could also be used to obtain information about elastic properties of ocular tissues. 10,11 According to the most widely accepted theory of presbyopia, the age-related loss of accommodation is attributed to gradual loss of lens elasticity. Furthermore, there is evidence that nuclear cataract lenses are generally harder than normal lenses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Previous methods for estimating lens sti®ness include spinning tests, [7][8][9] dynamic mechanical analysis, 10 indentation, 11,12 penetration, 13 Brillouin microscopy, [14][15][16][17][18][19] acoustic methods, 20,21 and compression. [22][23][24][25][26][27] The lens capsule has been mechanically characterized by in°ation testing 28,29 and uniaxial tensile testing.…”
Section: Introductionmentioning
confidence: 99%